1990
DOI: 10.1007/bf02284719
|View full text |Cite
|
Sign up to set email alerts
|

Differences in adaptive functioning among people with autism or mental retardation

Abstract: This report describes differences in motoric and instrumental activity of daily living skills (MADLs and IADLs) between 1,442 people with autism and 24,048 people with mental retardation, using data from an adaptive behavior measure. Comparisons were made using groups defined by age (5-12, 13-21, and 21-35 years) and intellectual level. Diagnoses of record were confirmed through group analyses of rates of problem behaviors consistent with autism and comparison to an independent data base. Findings suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 22 publications
2
21
2
2
Order By: Relevance
“…Since skill acquisition via social interaction and integration is profoundly inhibited and less accessible for autistic children, the rate of skill development can be expected to be less consistent over time for these individuals. Indeed, Jacobson and Ackerman (1990), drawing from a very large data base in New York, reported that the development of motoric and instrumental daily living skills was significantly more consistent across age groups for individuals with mental retardation than for those with autism.…”
Section: Discussionmentioning
confidence: 97%
“…Since skill acquisition via social interaction and integration is profoundly inhibited and less accessible for autistic children, the rate of skill development can be expected to be less consistent over time for these individuals. Indeed, Jacobson and Ackerman (1990), drawing from a very large data base in New York, reported that the development of motoric and instrumental daily living skills was significantly more consistent across age groups for individuals with mental retardation than for those with autism.…”
Section: Discussionmentioning
confidence: 97%
“…Although those with HFA and AS did not differ from each other in ADI-R or ADOS measures of restricted and repetitive behavior, both of these groups were more impaired in this domain than those with conduct disorders. Jacobson and Ackerman [1990] conducted a cross-sectional study of more than 20,000 individuals with mental retardation and 1,200 individuals with autism organized into child, adolescent, and adult cohorts. Data came from cases in the New York Developmental Disabilities Information System, which included reports of maladaptive behavior, including those reflective of autism (e.g., echolalia) as well as other domains of adaptive and maladaptive behavior.…”
Section: Restricted Repetitive Behaviors and Interestsmentioning
confidence: 99%
“…Of course, concerns about the accuracy of retrospective accounts of even the most knowledgeable informant cannot be discounted in such designs. Third, there have been several large-scale cross-sectional studies in which comparisons along behavioral dimensions have been made between children and adolescents or adults with autism [Jacobson and Ackerman 1990;Seltzer et al, 2003b]. As in all crosssectional studies, the confounding of age and cohort is a threat to internal validity.…”
mentioning
confidence: 97%
“…In een ouder onderzoek werd aangetoond, dat de kans op zelfverwondend gedrag bij een gelijk niveau van functioneren sterk aan de diagnose ASS was gerelateerd (Jacobson & Ackerman, 1990). Deze bevinding werd in een iets gemodificeerd onderzoek gerepliceerd (Kraijer, 1997).…”
Section: Comorbiditeit Met Een Autismespectrumstoornisunclassified